Emerging Role of 3.0 Tesla Cardiac Magnetic Resonance Imaging in Differentiating Cardiac Masses - Saif, Mohsin; Maken, Ghulam Rasool; Kamran, Javeria; Saeed, Nazish; Rehman, Waheed-Ur-; Chaudhary, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the role of Cardiac Magnetic Resonance Imaging in differentiating cardiac masses (thrombus vs tumor and benign tumor vs malignant tumor) in local population. Study Design: Analytical cross-sectional study. Place and Duration of Study: Tertiary Cardiac Care Center, Department of Cardiac Magnetic Resonance Imaging, Rawalpindi Pakistan, from Oct 2017 to Jun 2021. Methodology: This retrospective study included (n=56) patients via universal sampling, enrolled for Cardiovascular magnetic resonance imaging with a suspicion of cardiac masses either on echocardiography or Computed Tomography scan. Cardiovascular magnetic resonance imaging sequences were reviewed as SSFP cine images for mass location, size and mobility.T1 weighted turbo spin echo, T2 weighted turbo spin echo with and without fat saturation and TIRM sequences told their intensity as compared to normal myocardium, myomaps evaluated the relaxation time, while contrast first pass perfusion indicated the vascularity and delayed gadolinium enhancement images with standard and long TI were analyzed for contrast enhancement. Results: Total n=56 patients with a confirmed diagnosis of mass were included for the analysis. Mean age of participants was found to be 45.21(18.3%), height 168.4(8.69%) and weight 68.6(14.94%). There were 47(83.9%) males and females were 9(16.1%). 22(39.3%) had hypertension, 12(21.4%) had diabetes mellitus, 24(42.9%) had previous myocardial infarction. Maximum number of masses were found in LV 31(55.4%) followed by RV 11(19.6%). Sensitivity of T1 map to detect fibrosis intumor is 100%. Sensitivity of T2 map to detect edema in tumor is 82%. Conclusion: Cardiac masses like thrombi and tumors accurately diagnosed by cardiac MRI with etiology..